2009
DOI: 10.1136/jech.2008.082214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fibre intake on risk factors for cardiovascular disease in subjects at high risk

Abstract: Background: Epidemiological studies and feeding trials with supplements suggest that fibre intake is associated with a reduction in cardiovascular risk. However, the effects of changes in dietary fibre on risk factor levels have not been evaluated in free-living individuals. Thus, the effects of changes in dietary fibre intake on cardiovascular risk factors were assessed over 3 months in free-living high-risk subjects. Methods: 772 high-risk subjects (age 69¡5 years) were assigned to a low-fat diet or two Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 50 publications
(47 reference statements)
4
79
0
3
Order By: Relevance
“…It was 8 ± 4.46 gm and 5.6 ± 0.78 in men and women respectively. Epidemiological studies have found high fibre diets to have beneficial effects in the prevention of CVD [37]. High fat intake bears direct correlation with BMI and lipid profile of the subjects.…”
Section: Resultsmentioning
confidence: 99%
“…It was 8 ± 4.46 gm and 5.6 ± 0.78 in men and women respectively. Epidemiological studies have found high fibre diets to have beneficial effects in the prevention of CVD [37]. High fat intake bears direct correlation with BMI and lipid profile of the subjects.…”
Section: Resultsmentioning
confidence: 99%
“…4b) 18.20 % vs. 13.76 % respectively (p<0.05). There are numerous reports on dietary fiber potential lowering of blood cholesterol (Anderson et al 2009;Estruch et al 2009). The cholesterol reducing effect of SDF is based on different mechanisms.…”
Section: Determination Of Cholesterol and Sodium Cholate Absorption Cmentioning
confidence: 99%
“…One of the great challenges of the century in developed and developing countries has been avoiding the above-mentioned transition in the population´s dietary patterns. In the case of diet, several studies have shown that the components of dietary fiber, particularly soluble ones, may influence lipid metabolism in direct association between fiber intake and reduced risk of cardiovascular diseases (Estruch et al, 2009 There are several places in humans or animals where the dietary fiber may interact with physiological structures, such as the intestinal lumen, by modifying the kinetics of nutrient absorption through changes in solubility and pH or through post-absorptive ones such as modulation of pancreatic secretion, lipoprotein metabolism, secretion of bile acids or the effects of colonic fermentation by-products in the hepatic synthesis of cholesterol (Wong, De Souza, & Kendalli, 2006).…”
Section: Introductionmentioning
confidence: 99%